ACCOUNTING FOR OVERDISPERSION OF LETHAL LESIONS IN THE LINEAR QUADRATIC MODEL IMPROVES PERFORMANCE AT BOTH HIGH AND LOW RADIATION DOSES - Shuryak, Igor (Int J Radiat Biol, 2020)
PURPOSE: The linear-quadratic (LQ) model represents a simple and robust approximation for many mechanistically-motivated models of radiation effects. We believe its tendency to overestimate cell killing at high doses derives from the usual assumption that radiogenic lesions are distributed according to Poisson statistics. MATERIALS AND METHODS: In that context, we investigated the effects of overdispersed lesion distributions, such as might occur from considerations of microdosimetric energy deposition patterns, differences in DNA damage complexities and repair pathways, and/or heterogeneity of cell responses to radiation. Such overdispersion has the potential to reduce dose response curvature at high doses, while still retaining LQ dose dependence in terms of the number of mean lethal lesions per cell. Here we analyze several irradiated mammalian cell and yeast survival data sets, using the LQ model with Poisson errors, two LQ model variants with customized negative binomial (NB) error distributions, and the Padé-linear-quadratic and Two-component models. We compare the performances of all models on each data set by information-theoretic analysis, and assess the ability of each to predict survival at high doses, based on fits to low/intermediate doses. RESULTS: Changing the error distribution, while keeping the LQ dose dependence for the mean, enables the NB LQ model variants to outperform the standard LQ model, often providing better fits to experimental data than alternative models. CONCLUSIONS: The NB error distribution approach maintains the core mechanistic assumptions of the LQ formalism, while providing superior estimates of cell survival following high doses used in radiotherapy. Importantly, it could also be useful in improving the predictions of low dose/dose rate effects that are of major concern to the field of radiation protection.